1993
DOI: 10.2527/1993.7151187x
|View full text |Cite
|
Sign up to set email alerts
|

Lecithin in swine diets: I. Weanling pigs

Abstract: One digestibility experiment (Exp. 1) and two growth experiments (Exp. 2 and 3) were conducted to evaluate the use of lecithin as an emulsifier of soy oil and(or) an energy source in a two-phase starter diet program. Phase 1 consisted of d 0 to 14 postweaning, and Phase 2 consisted of d 14 to 35 postweaning. Diets were based on corn, soybean meal, and 20% dried whey and contained a constant ME:lysine level. In Exp. 1 and 2, two levels of lecithin (0 and 2%) at two levels of soy oil (0 and 6%) were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 0 publications
2
25
0
1
Order By: Relevance
“…Otherwise, Soares and Lopez-Bote (2002) did not observe any effects of dietary LPL supplementation on DM, CP and crude fiber in weanling pigs during the first 2 weeks after weaning or the following 2 weeks. Xing et al (2004) reported that the ATTD of DM, crude fat, CP and GE was increased with the addition of lard, similarly Overland et al (1993a) observed the addition of soy oil improved the ATTD of DM, GE, crude fat, and CP. Taken together, the increased fat digestibility in our study may contribute to the increased ATTD of DM, GE and N observed.…”
Section: Nutrient Digestibilitymentioning
confidence: 76%
See 2 more Smart Citations
“…Otherwise, Soares and Lopez-Bote (2002) did not observe any effects of dietary LPL supplementation on DM, CP and crude fiber in weanling pigs during the first 2 weeks after weaning or the following 2 weeks. Xing et al (2004) reported that the ATTD of DM, crude fat, CP and GE was increased with the addition of lard, similarly Overland et al (1993a) observed the addition of soy oil improved the ATTD of DM, GE, crude fat, and CP. Taken together, the increased fat digestibility in our study may contribute to the increased ATTD of DM, GE and N observed.…”
Section: Nutrient Digestibilitymentioning
confidence: 76%
“…The positive effects on growth performance could be the result of increased palatability with the addition of LPL or lecithin to the diets which caused a greater feed and energy intake (Overland and Sundstol, 1995). On the other hand, Overland et al (1993aOverland et al ( ,b, 1994 did not observe a benefit in weanling pigs or growing-finishing pigs on growth performance using soy lecithin. The effect of emulsifiers on growth performance may be more beneficial when animal fats are used (Overland et al, 1993a).…”
Section: Growth Performancementioning
confidence: 89%
See 1 more Smart Citation
“…However, the results are rather inconsistent. Improvements in fat digestibility and/or growth rate were noted by Jones et al, 35 De Rodas et al, 36 Superchi et al 37 and Jin et al,38 while no effects were noted by Frobish et al, 39 Van Wormer and Pollmann, 40 Øverland et al, 6 Reis de Souza et al, 41,42 Øverland and Sundstol, 43 Benatti et al 9 and Soares and Lopez-Bote. 44 The discrepancy is most likely attributable to differences in diet characteristics (mostly the fat fraction, type and level), to the type, fatty acid composition, level and mode of incorporation of the emulsifier and to antibiotics present in the diet.…”
Section: Resultsmentioning
confidence: 91%
“…In many other reports, the addition of fat at the diet was known to improve feed efficiency during the post-weaning period (Cera et al, 1988; 1990; Howard et al, 1990; Li et al, 1990; Overland et al, 1993; Tokach et al, 1995). However, initial stage (from 0 to 14 d after weaning) was also no difference of feed efficiency.…”
Section: Resultsmentioning
confidence: 99%